Application of TED-Ed Video Learning Application in IPS Learning in Senior High School - Mudzakir, Fuad; Ash-Shidiqi, Muhammad Ihsan; Wahyunengsih, Wahyunengsih (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study aims to explore the implementation of TED-Ed video-based learning in Social Studies (IPS) education at the senior high school level. Employing a qualitative approach with document analysis, this research examined various instructional artifacts such as lesson plans, instructional videos, and student assignments. The findings indicate that integrating TED-Ed videos significantly enhances students’ cognitive and affective engagement, particularly in understanding abstract social concepts such as democracy, globalization, and social justice. TED-Ed's structured narrative and engaging visuals were found to improve conceptual understanding, foster classroom participation, and enrich students’ written reflections. These findings align with the cognitive theory of multimedia learning and Vygotsky's social constructivist theory, emphasizing the effectiveness of multimodal and interactive learning experiences. However, the study also reveals that the success of TED-Ed implementation is highly dependent on teachers' digital literacy and their ability to contextualize video content within the national curriculum. A lack of professional training and unequal access to digital infrastructure remain key challenges in optimizing the platform's educational potential. Overall, TED-Ed has proven to be more than a supplementary visual aid—it is a transformative educational resource that supports student-centered learning and digital literacy in alignment with 21st-century educational demands.